Risk modification and preoperative optimization of vascular patients. Issue 4 (April 2022) - Goodman, Ben A.; Pichel, Adam; Danjoux, Gerard R.
Abstract: Major vascular surgery is associated with a high risk of morbidity and mortality. Targeted optimization of organ systems most likely to suffer morbidity should be made prior to elective surgery. Risk modification can reduce both perioperative and long-term complications. This article summarizes currently accepted best practice for risk modification and preoperative optimization prior to vascular surgery.